A method for measuring the attachment strength of the cestode Hymenolepis diminuta to the rat intestine. Issue 6 (4th November 2016) - Xie, W.; Racz, G.R.; Terry, B.S.; Gardner, S.L.
Abstract: A unique adaptation of many internal parasites of mammals is their ability to stay in the intestine for extended periods of time and resist the normal peristaltic movements and forces that push and expel material. To better understand parasite adhesion behaviour and replicate their attachment method in medical devices, an experiment was designed and performed using the rat tapeworm, Hymenolepis diminuta . The experiment employed a tensile test machine and a digital scale and was designed to calculate the attachment strength of the scolex to the mucosa through the change of the value of the digital scale during the tensile test. The attachment force of H. diminuta is 0.021 ± 0.011 g. This method could be applied in studies of parasite biomechanics and the results may help medical device researchers to better mimic the unique functional morphology of this species of parasite.